Propene Hydroformylation Reaction Catalyzed by HRh(CO)(BISBI): A Thermodynamic and Kinetic Analysis of the Full Catalytic Cycle. Issue 41 (20th October 2020) - Neto, Daniel H. Cruz; Dos Santos, Artur A. M.; Da Silva, Júlio C. S.; Rocha, Willian R.; Dias, Roberta P.
Abstract : In this article, full quantum mechanical calculations at the DFT‐D level were carried out to study the full catalytic cycle for the hydroformylation of propene, catalyzed by the [HRh(CO)(BISBI)] catalyst. All intermediates and transition states along the elementary steps of the whole catalytic cycle were located and properly characterized. The kinetic constants calculated from transition state theory together with the application of the steady‐state approximation were used to build a kinetic model for the hydroformylation reaction. The calculations show that regioselectivity of the reaction is set at the olefin insertion step, with the H2 oxidative addition being the rate‐determining step of the entire cycle, with an activation energy of 26.0 kcal.mol ‐1 for the linear pathway. The kinetic model showed that the CO gas acts as an inhibitor of the reaction at high pressure, and depending on the CO partial pressure, the rate of linear product formation is around 4 to 10 times faster. In line with experimental observations, our computational kinetic model indicated that at high CO partial pressures (> 40 atm), the HRh(CO)(BISBI) catalyst decreases its selectivity. Also was predicted from the computational kinetic model, that the reaction rates for both productions of normal and iso‐butanal are less sensitive to effects of H2 partial pressure concerning the observed with the variation of the partial pressure of CO gas. Abstract : This work presents a computational kinetic model for propene hydroformylation catalyzed by HRh(CO)(BISBI). Our model allows determining the reaction rate as a function of the concentrations and the partial pressures of the reactants. Simulating different reaction conditions with our model, we showed that CO acts as an inhibitor and that the oxidative addition of H2 is the rate‐determining step of the cycle.